DERADICALIZATION PROGRAM IN INDONESIA - sirait, osbenardus; Syauqillah, Muhamad; Hanita, Margaretha (UI Scholars Hub, 2021)
The deradicalization program arises because of the Indonesian government's anxiety or concern about the increasing number of understandings of radicalism and acts of terrorism that occur during society. The government chose to use a soft approach in the deradicalization program because they believed it could effectively rehabilitate former terrorist groups and their families from a radical mindset. The government hopes to live a peaceful life with the people in their neighborhood and will not repeat the acts of terror they have previously committed or become agents of radicalism. This study uses a qualitative method. The qualitative method will end in relevant conclusions, especially in the social and political fields, because of their complexity. The results of this study Efficient rehabilitation requires individual evaluation, systematic planning, and effectiveness benchmarks that we can look at in the preparation, implementation, and follow-up steps. The participation of convicts and facilitators, the availability of training methods and materials, and evaluation of the success of rehabilitation are part of the rehabilitation method.